PERFORMANCE MEASUREMENT OF â€œPANGGUNG LESTARIâ€ VILLAGE OWNED ENTERPRISE USING BALANCED SCORECARD APPROACH - Adana, Alif Haidir; Irham, Irham; Hardyastuti, Suhatmini (Jurnal Aplikasi Manajemen, 2019)
Development of Village economic has been entering a new era through the involvement of Village-Owned Enterprise (BUMDes), which can be an important part of the development. All this year, the measurement of BUMDes performance has only been assessed by the financial aspect and tends to ignore the non-financial aspects. It is not enough for management to adopt dynamic changes in the business environment. The purpose of this research was to analyze the performance of the BUMDes of Panggung Lestari from financial and non-financial aspects. The method of this research was using performance measurement with a Balanced Scorecard (BSC) approach. The results showed that the total performance of BUMDes Panggung Lestari was 84.78 percent, considered to be in very healthy category (AA). Although the performance of BUMDes Panggung Lestari was very healthy, the improvements in its performance are needed, especially in the perspective of the internal business process that has not optimal performance.